Place of commission of the so-called transit forbidden act - Filek, Bartłomiej Wojciech (The Opole Studies in Administration and Law, 2022)
The subject of the publication is the analysis of the place of comission of the so-called transit forbidden act. The publication explains the meaning of the concept of transit forbidden act and analyses the legal issue concerning the meaning of place of a causal link in determining the place of comission of the so-called transit forbidden act. The results of this analysis are important for determining the scope of application of the territoriality principle. The publication also presents de lege ferenda postulate concerning the analyzed issue.